Применение β-спектрометра тина мини-апельсин для спектрометрических исследований - Ж, Сэрээтэр (Scientific transaction of the National University of Mongolia. Physics, 2022)
The mini-orange magnetic spectrometry system for the measurement of conversion electron spectra and ey-coincidences has been described Mini- orange spectrometer efficiency for two types of magnets determined at distances 40 and 80 mm between the source and detector The efficiency increase and the effect elongation of the continuous background which connected with the positron radiation have been demonstrated using the mini-orange on the 147Tb (T1/2=1.7h) conversion electron spectrum in the energy range 1-2 MeV. The possible other applications of the mini-orange spectrometry system are discussed.